2006
DOI: 10.1038/nm1419
|View full text |Cite
|
Sign up to set email alerts
|

Generation of C5a in the absence of C3: a new complement activation pathway

Abstract: Complement-mediated tissue injury in humans occurs upon deposition of immune complexes, such as in autoimmune diseases and acute respiratory distress syndrome. Acute lung inflammatory injury in wild-type and C3-/- mice after deposition of IgG immune complexes was of equivalent intensity and was C5a dependent, but injury was greatly attenuated in Hc-/- mice (Hc encodes C5). Injury in lungs of C3-/- mice and C5a levels in bronchoalveolar lavage (BAL) fluids from these mice were greatly reduced in the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
736
3
15

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 869 publications
(794 citation statements)
references
References 26 publications
29
736
3
15
Order By: Relevance
“…Since both these activating products can be blocked by C3 inhibition, we confirmed that the activation was due to an initial activation by C3 and not a direct activation of C5, which could be an alternative mechanism [27]. The difference between the liquefied and solid core microcapsules to induce cytokines, and their opposite effects to trigger TCC and C5a show that the cytokine secretion was not caused by TCC or C5a under the current conditions.…”
Section: Cd11b Cd18 or Cd11c Blockagesupporting
confidence: 61%
“…Since both these activating products can be blocked by C3 inhibition, we confirmed that the activation was due to an initial activation by C3 and not a direct activation of C5, which could be an alternative mechanism [27]. The difference between the liquefied and solid core microcapsules to induce cytokines, and their opposite effects to trigger TCC and C5a show that the cytokine secretion was not caused by TCC or C5a under the current conditions.…”
Section: Cd11b Cd18 or Cd11c Blockagesupporting
confidence: 61%
“…We discovered that C5 functions independently of C3 to induce early neutrophil recruitment during infection with MVA, a nonreplicating viral vector known to activate the innate immune system (27). C5 may be activated by proteolytic enzymes such as serine proteases released from phagocytic cells (21), as we observed no differences in C3-deficient mice treated with antithrombin III (data not shown), ruling out thrombin-mediated activation (25). Activation of C5 by locally released proteases could serve to rapidly amplify the local immune response, as C5a induces inflammatory cytokine expression and is chemotactic for leukocytes.…”
Section: Discussionmentioning
confidence: 85%
“…C3-independent activation of the complement C5 component has been known for some time (21)(22)(23)(24)(25). However, the relevance of these C3-independent pathways in vivo is not well studied and was never considered in the context of viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of such crosstalks in inflammation are increasing and the research in this field is expanding. For instance has thrombin of the coagulation cascade been shown to directly cleave C5 of the complement system to C5a in the absence of C3 (132), indicating that C5a and TCC may be generated in the absence of upstream complement activation. C5a has been shown to induce the spark plug of coagulation, TF, both on endothelial cells and neutrophils (89,133).…”
Section: Inflammation In Sepsismentioning
confidence: 99%